Mapping responsible conduct in the uncharted field of research-creation: A scoping review. (4th July 2019) - Voarino, N.; Couture, V.; Mathieu-Chartier, S.; Bélisle-Pipon, J. C.; St-Hilaire, E.; Williams-Jones, B.; Lapointe, F. J.; Noury, C.; Cloutier, M.; Gauthier, P.
ABSTRACT: This scoping review addresses the issues of responsible conduct of research (RCR) that can arise in the practice of research-creation (RC), an emergent, interdisciplinary, and heterogeneous field at the interface of academic research and creative activities. Little is yet known about the nature and scope of RCR issues in RC, so our study examined three questions: (1) What are the specific issues in RC in relation to RCR? (2) How does the specificity of RC influence the understanding and practice of RCR? (3) What recommendations could help address the issues highlighted in the literature? To answer these questions, we conducted a scoping review of the academic literature ( n = 181 texts) dealing with RCR in RC. We found that researcher-creators faced some very different RCR challenges in comparison with their colleagues in the rest of academia. Addressing these issues is important for both the RCR and RC communities in order to ensure that the rapid development of this field occurs in line with the norms of RCR which, nonetheless, should be adapted to respect the particularities of RC and allow its contributions to the academic world.